Pemberian Tepung Azolla Microphylla (Paku Air) Yang Terfermentasi Dalam Ransum Terhadap Recahan Karkas Ayam Kampung Super Umur 10 Minggu - I Ketut Ari Krisna Sanjaya; Ni Ketut Etty Suwitari; Ni Made Yudiastari (Fakultas Pertanian, Universitas Warmadewa, 2024)
Super village chicken is one of the increasingly developed meat-producing commodities. To this productivity, it must be supported by a high-quality feed, one of which is the Azolla Microphylla. The goal is to find out at what level the use of fermented Azolla Microphylla flour will show the best results against the cracks of the 3 to 11 weeks old super village chicken carcass. The scheme used in this study is the Complete Random Scheme (RAL) with 5 treatments and 3 repetitions. Ransum contains 3% Azolla Microphylla fermented flour, K2 is Ransom contains 6% Azolla Microfylla Fermented Powder, K3 is K3 contains 9% azolla microphyllla fermentiated flour and K4 is K4 contains 12% azola microphylle fermentation flour. Each repetition (experimental unit) used 5 super village chickens, so the total number of super villages chicks used in this study was 75. Giving fermented Azolla Microphylla flour in ransom showed an unrealistic influence (P>0,05) on the cracking of the super-week-old village chicken carcass, giving Azolla microphyla flour ferments in super-village chicken runs optimally at a 3% yield level.